ДЕЦЕНТРАЛИЗАЦИЯ ИМУЩЕСТВА И ПОЛНОМОЧИИ – КОНСТИТУЦИОНЫЙ ПРИНЦИП ПУБЛИЧНОГО УПРАВЛЕНИЕ - Сосна, Александру; Михалаш, Виктория (CEP USM, 2018)
The article highlights the decentralization of property and powers stipu- lated by the Law of the Republic of Moldova No. 68 of 05.04.2012 on the ap- proval of the National Strategy for Decentralization and the action plan for the implementation of the National Strategy for Decentralization for 2012-2018. This law determines the goals and objectives for the implementation of the priority associated with the decentralization of power and the provision of local autonomy in accordance with the European Charter of Local Self-Gov- ernment of 15.10.1985, which was ratified by the resolution of the Parliament of the Republic of Moldova No. 1253-XIII of 16.07.1997. The relevance of the topic is due to the need to improve the quality of the activities of local public administration by transferring to them from the cen- tral public administration authorities a part of the functions and powers, as well as the property necessary to fulfill the functions and powers transferred to them, as well as responsibility

В статье освещается децентрализация имущества и полномочий, предусмотренная законом РМ № 68 от 05.04.2012 года «Об утверж- дении Национальной стратегии децентрализации и плана действий по 119 внедрению Национальной стратегии децентрализации на 2012 – 2018 годы». Данный закон определяет цели и задачи по реализации приоритета, связанного с децентрализацией власти и обеспечения местной автоно- мии в соответствии с Европейской хартией местного самоуправления от 15.10.1985 года, которая была ратифицирована постановлением Парламента РМ № 1253-XIII от 16.07.1997 года. Актуальность темы обусловлена необходимостью улучшения качес- тва деятельности органов местного публичного управления путём пере- дачи им от центральных органов публичного управления части функций и полномочий, а также имущества, необходимого для выполнения пере- данных им функций и полномочий, а также ответственности.
Keywords: decentralization; property; property right; local public administration authorities; administrative-territorial unit; public property; state property; property of administrative-territorial units; property belonging to a private sphere; децентрализация; имущество; право собственности; органы местного публичного управления; административно-территориальная единица; публичная собственность; собственность государства; собственность административно-территориальных единиц; имущество; относящееся к частной сфере